A MINE SAFETY MANAGEMENT FOR FATIGUE ACCIDENT PREVENTION AT PT SEMESTA ALAM BARITO SITE - Dedy Waliyan Dewa (Departemen K3 FKM Universitas Halu Oleo, 2025)
The Mining Safety Management System was established by the Government of the Republic of Indonesia through the Ministry of Energy and Mineral Resources as a reference for companies to ensure that operations are conducted safely so that production, sales and government revenues from the mineral and coal sector are sustainable. The principle is that production is the ultimate goal, while safety is the means or method. One aspect of mine safety that is part of good mining practice is fatigue management. This is because fatigue is one of the causes of accidents among workers operating mobile equipment in mining operations, which can result in fatalities and production stoppages. The purpose of this study is to evaluate the implementation of fatigue management in workers to prevent mining accidents at the site of PT Semesta Alam Barito, which has a remote area character. The methodology used by the author in this study is a descriptive and observational qualitative method of work practices in the company and then improvements are made to improve the quality of the fatigue prevention program in the field. The results of this study indicate that a comprehensive and consistent fatigue management program by the company and work partners, applied to workers before work begins, during work, and after work, can prevent fatigue-related mining accidents.